RELATIONSHIP BETWEEN THE NINE FUNCTIONS OF PROJECT MANAGEMENT AND PROJECT SUCCESS - Hafnidar Abdul Rani; Che Sobry Abdullah; Shahimi Mohtar (JURNAL TEKNIK SIPIL, 2012)
Abstract: This research investigates the relationship between project management function and project success. Project management function element is operationalized by nine constructs. Data was collected using questionnaire survey approach. This study employed stratified random sampling procedure in selecting the construction organizations for inclusion in the sample. Four hundred and forty eight Aceh construction organizations participated in this study. Descriptive analysis, factor and reliability analysis, Pearson correlation analysis and multiple regression methods of data analysis were utilized for hypotheses testing. The results revealed that all the project management function dimensions and associated positively with project success dimensions.Keywords : Project management; project management function; Project Management Body of Knowledge; project success.Abstrak: Penelitian ini menyelidiki hubungan antara fungsi manajemen proyek dan kesuksesan proyek. Elemen fungsi manajemen proyek dioperasionalkan oleh sembilan konstruk. Data dikumpulkan dengan menggunakan pendekatan survei kuesioner. Penelitian ini digunakan prosedur stratified random sampling dalam memilih organisasi konstruksi untuk dimasukkan dalam sampel. Empat ratus empat puluh delapan organisasi konstruksi Aceh berpartisipasi dalam penelitian ini. Analisis deskriptif, analisis faktor dan keandalan, analisis korelasi Pearson dan analisis regresi berganda yang digunakan untuk pengujian hipotesis. Hasil penelitian menunjukkan bahwa semua dimensi fungsi manajemen proyek berhubungan positif dengan dimensi kesuksesan proyek.Kata kunci : Manajemen proyek; fungsi manajemen proyek; Project Management Body of Knowledge; kesuksesan proyek.